The Effect of Person-Organization Fit and Person-Job Fit on Performance with Organizational Citizenship Behavior as Mediation - Purbaningrum, Nila Widi; Tjahjaningsih, Endang (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to examine the impact of job fit and person-organization fit on performance, using organizational citizenship behavior as a mediating factor. This study approach is quantitative. The type of research used in this research is primary data. The population of this study consisted of 338 employees at Perumda Air Minum Tirta Moedal Semarang City. Sampling was done by purposive method and the sampling technique applied was the Slovin formula, so that the number of samples in this study was 90 respondents. The analysis technique uses a statistical package for social science (SPSS) software version 25. The results of this study indicate that Person Organization Fit, Person job fit affects Organizational Citizenship Behavior. Person Organization Fit does not have a significant impact on employee performance. Person Job Fit and Organizational Citizenship Behavior affect employee performance. Organizational Citizenship Behavior can mediate the impact between Person Organization Fit on employee performance. Organizational Citizenship Behavior can mediate the impact of a Person's Job Fit on employee performance.